An Analytical Study for Some Variables Index of Biomechanical Aiming Skill for Corner Handball Players - A. Neamah Al-Jadaan, Dhurgham; Sabeeh Mustafa, Usama; Shenein Munahi, Kamil (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to design a test to measure the preforming accuracy of the aiming skill from the corner of hand ball. 2 - Identify an indicator of the values of some biomechanical variables for the aiming skill of the corner players with a handball. The descriptive method was used by using the survey method to solve the research problem. The research sample included some specialized school players of handball for the sport season 2019-2020 and the number was (6) players. The researchers contacted a design to measure the accuracy of aiming pass for corner player to adopt it as a test to evaluate the performance of the players, in order to get precise results in the biomechanical analysis, because we adopt the successful attempt to come with biomechanical varieties. The main experiment of the research has been conducted in 3/7/2019 on research sample. A video camera was used during the experiment and a special program for sport skills analyzing was used (kinovea) 18th issuance to elicit some of the biomechanical varieties. After treating the data using a computer according to statistical program SPSS 21 Ver. A set of outcomes have been reached: 1. Speed has the essential and major role for the biomechanical variables which were studied in the research, and therefore we note that the results are not at the required level because the player moves somewhat a short distance somewhat without performing another skill such as plumping during running and thus needs a great distance to long his speed. 2. The slow transition during the supporting and pushing process leads in a slower transition during the joints of the body and then the tool and thus the speed of the ball was not good.